2009
DOI: 10.1016/j.copbio.2009.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic imaging in humans with near-infrared fluorescence

Abstract: SummaryWhile the lymphatic system is increasingly associated with diseases of prevalence, study of these diseases is difficult owing to the paucity of imaging techniques with the sensitivity and temporal resolution to discriminate lymphatic function. Herein, we review the known, pertinent features of the human lymphatic system in health and disease and set the context for a number of emerging studies that use near-infrared fluorescence imaging to non-invasively assess tumor draining lymphatic basins in cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
199
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(209 citation statements)
references
References 39 publications
(48 reference statements)
4
199
1
5
Order By: Relevance
“…These recommended doses of ICG administrated in adults correspond to 1.15-5.16 μM of ICG concentration in the brain tissue. Furthermore, it can be found in earlier publications that the typical ICG dose per measurement used in in-vivo experiments does not exceed 20 mg (corresponding to 2.58 μM concentration of ICG in the brain) [26,27,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. However it can be also found that some groups used 25 mg (3.83 μM in the brain) in a single dose [60][61][62][63][64] and even higher doses of ICG 0.5 mg/kg were reported in studies on humans [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…These recommended doses of ICG administrated in adults correspond to 1.15-5.16 μM of ICG concentration in the brain tissue. Furthermore, it can be found in earlier publications that the typical ICG dose per measurement used in in-vivo experiments does not exceed 20 mg (corresponding to 2.58 μM concentration of ICG in the brain) [26,27,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59]. However it can be also found that some groups used 25 mg (3.83 μM in the brain) in a single dose [60][61][62][63][64] and even higher doses of ICG 0.5 mg/kg were reported in studies on humans [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other lymphatic imaging approaches described in Table 1, NIRF lymphatic images can be collected rapidly with millisecond acquisitions (33), allowing for the non-invasive interrogation of function in collecting and conducting lymphatic vessels (40,45,46) and the quantitative assessment of the lymph pump frequency and apparent velocity in the collecting and conducting lymphatics of both mice and humans (Supplemental Videos 1 and 2; supplemental material available online with this article; doi:10.1172/JCI71612DS1). The mechanism for lymph pumping, an intrinsic property of the lymphatic muscle, is due in part to the rhythmic constriction/relaxation cycle of vascular smooth muscle cells, called lymphangions, that are bounded by valve leaflets that open and close in an orchestrated manner to mediate unidirectional, efficient lymph flow (reviewed in ref.…”
Section: Imaging Techniques To Assess Lymphatic Functionmentioning
confidence: 99%
“…While investigational camera designs have widely varying sensitivity (34,35), non-invasive NIRF imaging can detect the lymphatic vasculature located as deep as 3-4 cm beneath the tissue surface with as little as 10 μg of ICG in 0.1 ml in humans (36) using intensified camera technologies, and up to 5 μg of ICG in 10 μl in mice using electron multiplier CCD technology (37)(38)(39). In clinical studies, NIRF imaging using ICG has been demonstrated to detect subclinical lymphedema (40,41) to guide and assess lymphatico-venous anastomosis microsurgery in a case of lower extremity lymphedema (42), and has been found to be superior to lymphoscintigraphy in the diagnosis of lymphedema (43). Because lymphatic vessel reconstitution plays an important role in transplantation, NIRF imaging of the lymphatics with ICG has also been used to assess tissue rejection in an animal model of hind limb transplantation (44), suggesting potential uses in clinical regenerative medicine.…”
Section: Imaging Lymphatic Architecture In Humans and Micementioning
confidence: 99%
“…This is called Near Infra-Red Florescence Imaging (NIR). NIR-ICG can pick up early stages of lymphedema and diagnose diseased non-contracting lymphatics even before swelling occurs Adams et al;Rasmussen et al, 2009Rasmussen et al, , 2010Unno et al, 2010;Maus, 2010) There is a variety of diagnostic tests that can be performed in order to classify and detect lymphedema. These include soft tissue imaging, bioimpedance spectroscopy, tonometry, genetic testing, various forms of vascular imaging, as well as blood tests .…”
Section: Diagnosis Of Lymphedemamentioning
confidence: 99%